Evolution of the human tongue and emergence of speech biomechanics - Ekström, Axel G.; Edlund, Jens (Frontiers in Psychology, 2023)
The tongue is one of the organs most central to human speech. Here, the evolution and species-unique properties of the human tongue is traced, via reference to the apparent articulatory behavior of extant non-human great apes, and fossil findings from early hominids – from a point of view of articulatory phonetics, the science of human speech production. Increased lingual flexibility provided the possibility of mapping of articulatory targets, possibly via exaptation of manual-gestural mapping capacities evident in extant great apes. The emergence of the human-specific tongue, its properties, and morphology were crucial to the evolution of human articulate speech.